Design and Development of Micro Vertical Axis Wind Turbine for Rural Application (International Journal of Engineering and Computer Science, 2014)
In this paper we describes what is micro vertical axis wind turbine and its importance in energy production. This paper describes briefly the design consideration of vertical axis wind turbine with the aim to start or work in very low speed of wind. The model has been develop and fabricated in this project. The aim is to make micro axis wind turbine which can be installed at rural areas where electricity crises is the main problem. The effort has been taken to design the VAWT which can work at very low wind speed of 2 m/s.